NAVIGATING PROBLEM-BASED LEARNING CHALLENGES IN PEKALONGAN SECONDARY EFL READING CLASSROOMS - Munazihah Munazihah; Rahayu Puji Haryanti (Universitas Islam Sumatera Utara (UISU), 2026)
This study investigates the systemic and pedagogical challenges faced by English teachers in implementing Problem-Based Learning (PBL) under the Kurikulum Merdeka. Grounded in a qualitative design, data were collected from nine EFL teachers in Pekalongan Regency through interviews, observations, and pedagogical audits. The analysis employed Miles and Saldaña’s (2018) interactive model and Fullan’s (2015) theory of educational change. The findings reveal two interrelated barriers: chronic resource deprivation and a prevalent state of 'False Clarity.' This conceptual ambiguity occurs when teachers adopt the PBL label without its analytical substance. Consequently, these constraints compel teachers to revert from facilitators of inquiry to translators of content. This shift effectively pushes learners into a 'Zone of Frustration' where linguistic barriers stifle critical engagement. The study highlights the urgent need for contextually grounded teacher training and equitable infrastructure investment to foster sustainable educational reform.